THE EFFECT OF PROFESSINALISM, ETHICS, AND INDENPEDENCY ON MATERIALITY JUDGMENT IN AUDITING PROCESS - Fitrinnisak, Alfina; Ludigdo, Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The aim of this study is to investigate how the effect of professionalism, ethics, and indepedence on materiality judgment at CPA firm in East Java Province. This study employed a quantitative approach in carrying out data analysis, the method of analysis used in analyzing the emperical data collected by researchers to providing empirical evidence on the effects of auditor professionalism on materiality judgment. Second, provide empirical evidence on the professional ethics on materiality judgment. Third, provide empirical evidence effect of independency on materiality judgment, and provide empirical evidence of auditor professionalism, ethics, and indepedency stimultaneously on materiality judgment Population of this research are auditors who works at CPA firm in East Java Province. Sampling method of this research is using purposive sampling. This research using multiple linear regression and single linear regression analysis The results showed that both partially and simultaneously, professionalism has a effect on materiliaty judgment in auditing process, ethics mostly significant effect on materiality judgment in auditing process and the last is independency has a significant effect on the materiality judgment which mean all variable has a significant effect to materiality judgment stimultaneously. Suggestion for further research, other researchers can make this title as qualitative approach and also make separated sample between CPA big four or non CPA big four.This study also indicates that the auditor ethics variable is most dominant influence on consideration of the level of materiality in the auditing process. Keywords: Professioanlism, Ethics, Indepedency and Materiality Judgment